The Khonji Dialect of Lārestān - Borjian, Habib (Journal of Iranian Linguistics, 2024)
Southwest Iranian languages are significantly underrepresented in academic literature, lacking comprehensive descriptions. This paper aims to fill this gap by examining the Lārestāni language variety spoken in Khonj, which is otherwise poorly known. In phonology, it is shown that uvular stops and fricatives have only recently infiltrated the Khonji sound system. Khonji stands out in the construction of noun phrases due to the presence of a deictic suffix and an intricate system of adpositions. The verb inflection in Khonji is notable for its ten identified aspectual and modal affixes. Combinations of these affixes give rise to a system of five simple tenses (surpassing the previously identified four), alongside corresponding progressive tenses, supplemented by at least four identified subjunctive tenses. The binary stative-dynamic distinctions in posture verbs, as illustrated in a diagram for 'sit', align more closely with English than Persian. Ergativity is prominently manifested through two sets of person markers, creating phrases similar to Middle Persian and counterintuitive to New Persian. Experiencer constructions characterize the expressions of possession and modals in the language.
Keywords: Southwest Iranian; phonology; morphosyntax; subjunctive; ergative; stative verbs